Optical coherence tomography-based retinal vessel analysis for the evaluation of hypertensive vasculopathy - Schuster, Alexander K.; Fischer, Joachim E.; Voßmerbäumer, Urs (Acta ophthalmologica, 2015)
Purpose: Evaluation of retinal vessels in cardiovascular disease traditionally relies upon funduscopy, but more recently digital photo analysis has expanded the spectrum. As spectral domain optical coherence tomography (OCT) allows an in-vivo assessment of retinal tissue and its vessels on a histological scale, our study aimed at using this tool for the analysis of the retinal vasculature. Methods: Circumferential peripapillary OCT scans (3DOCT-2000; Topcon Inc., Tokyo, Japan), with centration on the optic nerve head, were taken from 20 eyes (20 participants) with normal blood pressure and 20 eyes (20 participants) with arterial hypertension above 120 mmHg (mean blood pressure). The diameter of all vessels intersecting the scan line was measured in the OCT and used to calculate central vessel equivalents, and the A/V ratios were calculated. Bland-Altman analysis was performed to evaluate reliability. Correlation coefficients were determined for reliability of the method as well as with the individual mean arterial blood pressures. Results: Forty eyes (40 participants) were included in the study. Mean arterial blood pressure was 96 ± 4 mmHg in the control group and 132 ± 7 mmHg in the hypertonic group. Mean A/V ratio as determined from OCT scans was 0.82 ± 0.13 (normotonic) versus 0.62 ± 0.11 (hypertonic). A Pearson's correlation coefficient of 0.67 (p < 0.001) was determined between A/V ratio and blood pressure. Conclusions: Our results highlight the feasibility of retinal vessel measurements in spectral domain OCT. A relation between mean arterial blood pressure and OCT-based A/V ratio was established. Further research will elucidate influencing factors and provide a broader basis for therapeutic approaches.
Gesehen am 12.10.2017